Diagnosis and treatment of cryptorchid testicular torsion in children: A 12-year retrospective study - Chen, Pengyu; Yang, Zhilin; Chen, Nana; Liu, Lei; Su, Jiahong; Sun, Mengkui; Li, Shoulin (Frontiers in Pediatrics, 2022)
Purpose: To investigate the clinical characteristics, treatment, and prognosis of cryptorchid testicular torsion in children. Methods: From January 2010 to December 2021, the clinical data of 25 children with cryptorchid testicular torsion were reviewed. The median age was 64.5 months, ranging from 2 months to 15 years. All patients had unilateral torsion and the duration of symptoms ranged from 3 hours to 192 hours. Results: Among the 25 cases, 5 cases were treated with orchidopexy and 20 cases were treated with orchiectomy. At postoperative follow-up from 6 months to 8 years, 20 patients with orchiectomy had well-developed testes on the healthy side. Four of the five patients who underwent orchidopexy on the affected side had well-developed testes bilaterally, and one had testicular atrophy. Conclusion: Cryptorchid testicular torsion is a rare urological emergency that is prone to delayed presentation and misdiagnosis. Clinicians need to take a careful patient history, perform a thorough physical examination and combine ultrasound findings to make a clear diagnosis. Active testicular exploration is required for patients suspected of cryptorchid testicular torsion, and orchidopexy or orchiectomy is chosen depending on the intraoperative situation.